1993
DOI: 10.1002/1097-0142(19930915)72:6<1991::aid-cncr2820720633>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors and cathepsin d in human thyroid tissue

Abstract: Background. To investigate the significance of estrogen receptors (ER) in the pathogenesis of thyroid dysplasia, the authors analyzed, by analogy with breast cancers, ER and three estrogen‐regulated proteins: progesterone receptor (PR), cathepsin D, and pS2 protein, in cytosols of 42 human thyroid tissues. Methods. ER and PR were measured by an immunoenzymatic assay and cathepsin D and pS2 by an immunoradiometric assay. Tissue specimens included 7 normal tissues, 6 benign nodules, 8 toxic adenomas, 7 from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Cat D was studied in human primary breast cancer, and enzyme overexpression was found to be associated with an increased risk of metastasis and shorter survival (3,4). A similar association was identified in thyroid (5) and skin (6) cancer.…”
Section: Introductionsupporting
confidence: 74%
“…Cat D was studied in human primary breast cancer, and enzyme overexpression was found to be associated with an increased risk of metastasis and shorter survival (3,4). A similar association was identified in thyroid (5) and skin (6) cancer.…”
Section: Introductionsupporting
confidence: 74%
“…Sex hormone steroid receptors have been identified in normal mammalian thyroid tissues and in those with pathological changes, and it has been reported that estrogen and androgen might be associated with promoting and inhibitory effects, respectively, on thyroid tissues. [61][62][63][64] This may account for the significantly greater thyroid volume observed in female dolphins at the adolescent and adult stages.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that focal NE differentiation frequently occurs in prostatic adenocarcinoma and it may have significant prognostic implications [12-14]. NE differentiation is also described in hormone refractory prostate cancer; Krijnen et al [14] noted that androgen receptors are not present in prostatic adenocarcinoma staining positive for CgA.…”
Section: Discussionmentioning
confidence: 99%